Purabaya Bus Station Service Performance in New Adaptation Period - Putu Cinthya Pratiwi Kardita; Achmad Wicaksono; M. Ruslin Anwar (Journal of Infrastructure & Facility Asset Management, 2021)
The significant losses in the transportation sector, especially the inter-city, with-in-province bus (AKDP) and the inter-city inter-province bus (AKAP) operating at the Purabaya Bus Station during the COVID-19 pandemic, mostly because less bus operated due to a significant decrease in passengers' numbers. This situation is the impact of implementing the Large-Scale Social Restrictions (PSBB) policy in the Surabaya Metropolitan Area from April 28th to June 8th, 2020. The COVID-19 case is still increasing, but the economy needs to be saved; therefore, Indonesia has begun to enter a New Adaptation Period. During this period, bus movements' increase is less than 5%, while passengers are less than 2% of the typical Purabaya Bus Station's normal situation. The 24 (twenty-four) hours bus station operational services is following health protocols. They have a tight schedule for site sterilization by spraying disinfectants, checking passenger temperatures with a thermal camera, checking health documents for passengers and fleet crews, providing handwashing and disinfecting booths before entering the waiting room, and applying physical distancing between passengers. However, online ticket purchases are currently only for AKAP buses, while for AKDP buses, the passengers still apply on bus payment to the bus crew.